Kernel-type estimator for the extreme value index of air temperature - Jokimaitis, Arvydas; Petronaitis, Darius (Lietuvos matematikos rinkinys, 2017)
The article authors obtained of kernel-type estimator for the extreme value index of maximum air temperature.